Interactive Environments an Investigation into Real-Time Responsive Spatial Systems - Biloria, Nimish (ICONARCH International Congress of Architecture and Planning, 2014)
The design-research work illustrated in this article is centred on the emerging field of Interactive Architecture. The real-time information exchanging spatial outputs showcased in the paper demonstrates a fusion between the human, the material, the electronic and the digital domains. This fusion is explicitly attained through a synergistic merger between the fields of human psychology, embedded sensing and control systems, ubiquitous computing, architectural design, kinetic systems and computation. The resultant interactive projects attain the dimension of complex adaptive systems, continually engaged in activities of data-exchange resulting in physical and ambient adaptations of their constituting components in response to contextual variations. Interdependent componential networks, where every constituent component of a spatial prototype becomes a potential information hub by means of its ability to collect, process and communicate contextual data. Apart from this, the components themselves operate, as an actuated detail owing to their ability to kinetically re-position themselves in three-dimensional. A strategy apt for binding physical with the digital and the human counterpart is thus illustrated via selected research and design projects conducted at Hyperbody, TU Delft, The Netherlands.